Double burden of malnutrition: The role of framing in development of political priority in the context of rising diet-related non-communicable diseases in Tamil Nadu, India (P22-005-19) - Constantinides, Shilpa; Blake, Christine E.; Frongillo, Edward A.; Avula, Rasmi; Thow, Anne-Marie (Oxford University Press, 2019)
In low- and middle-income countries, non-communicable disease (NCD) prevalence is increasing while undernutrition persists, resulting in a double-burden of malnutrition. How policy actors frame malnutrition may shape policy, programming, and investment. In India, where NCDs are rising rapidly and undernutrition persists throughout the country, much of food and health policy is decentralized, but little is known of how the double burden of malnutrition is understood at the state level. This study aimed to identify and compare frames and priorities for nutrition used by relevant policy actors to help understand the narrative emerging around policy solutions for the double burden of malnutrition.